Rod v jazyke vs. gender v soznanii (kognitivnye i sociopsihologičeskie aspekty) - Norman, Boris Justinovič (Slavistična revija, 2019)
This article investigates the relationship between the lexical meaning of a word and its grammatical gender in Russian. Examples are furnished to show how a person tries to systematize the surrounding world in accordance with his/her gender stereotypes; to do this, he/ she uses markers of grammatical gender
Keywords: biološki spol; gender; grammatical gender; psihološki spol; Russian language; ruščina; sex; slovnični spol